Managing the wealth of nations political economies of change in preindustrial Europe - Rössner, Philipp Robinson 1977- (Bristol University Press, 2023)
"‘Commerce and manufactures gradually introduced order and good government,’ wrote Adam Smith in his Wealth of Nations, ‘and with them, the liberty and security of individuals.’ However, Philipp Robinson Rössner shows how, when looked at in the face of history, it has usually been the other way around. This book follows the development of capitalism from the Middle Ages through the industrial revolution to the modern day, casting new light on the areas where premodern political economies of growth and development made a difference. It shows how order and governance provided the foundation for prosperity, growth and the wealth of nations. Written for scholars and students of economic history, this is a pioneering new study that debunks the neoliberal origin myth of how capitalism came into the world."
Keywords: Geschichte 1250-1850; Wirtschaft; Politische Ökonomie; Kapitalismus; Europa